Use of digital games in the third age: A systematic review - Augusto Souza dos Santos, Matheus; dos Santos de Jesus, Bruna; Simões Ferreira, Joacir; Cláudio Machado dos Santos, Luiz; Vera Cruz Diniz, Marcelo (Seven Editora, 2023)
Population aging is a global phenomenon that brings significant challenges to society. Increasing life expectancy and decreasing birth rates have led to the growth of the elderly population worldwide. In Brazil, this trend is no different, with projections indicating an increase in the number of elderly in the coming decades. In this context, the cognitive health of the elderly plays a crucial role, as it can be negatively affected by aging, impacting their quality of life and autonomy. Given these issues, the use of digital games as cognitive stimulation tools has aroused growing interest in the area of health and technology. These games offer entertainment opportunities and cognitive challenges that can promote the health and well-being of seniors, as well as slow or prevent the cognitive decline associated with aging. However, many digital gaming solutions on the market have limitations in terms of diversity, customization, usability, and accessibility for aging users. In this article, a systematic review of the literature on the application of digital games to the elderly was carried out, focusing on the age group of 60 to 75 years. The review covered studies that investigated the effects of digital games on the cognitive health of the elderly, as well as the limitations found in existing solutions. In addition, a proof of concept of a gaming device based on the Arduino platform was proposed, aiming to fill the identified gaps. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-070